A neural network assisted algorithm for automated detection of breast cancer nuclei - Tsapatsoulis, Nicolas; Schnorrenberg, Frank; Pattichis, Constantinos S.; Kollias, Stefanos D.; Schizas, Christos N. (My University, 1997)
A neural network assisted algorithm used for the detection of nuclei in biopsy images is presented. This algorithm is combined in a logical AND form with an algorithm based on receptive fields to build the nuclei detection part of an integrated system used for automated assessing of histological slides of breast biopsy specimens
Keywords: Breast biopsy; Breast cancer; Cancer detection; Detection algorithms; Immune system; Medical treatment; Neural networks; Object detection